Luis Barragán and the invention of Mexican Regionalism - MELA, Giulia (2018)
The work of Luis Barragán (1902-1988) embodies Mexican identity, and the architect is considered one of the most important figures of the Critical Regionalism movement in Latin America. Nevertheless, a comprehensive analysis of his own private library–kept at the Barragan Foundation, Switzerland and Fundación de Arquitectura Tapatía Luis Barragán, Mexico–tells a different story. In fact, the contemporary critical reception of his work has a far more complex genesis, which might be summarised as follows: 1. Barragán, nemo propheta in patria. For many years, Barragán’s work was better known abroad than in his own country. The national recognition came in 1976, with the Premio Nacional de Ciencias y Artes, after an exhibition at the MoMA in New York. At that time, Barragán was a 74-year old architect that had realized some of his most famous projects, such as the Casa Barragán, Tlalpan Chapel, Cuadra San Cristóbal, and Casa Gilardi. 2. Barragán, forger of an independent path. The urban project for Jardines del Pedregal was the turning point of Barragán’s career, and from the mid-1940s the architect distanced himself from the research path of his colleagues. His detachment from the academic, political, and theoretical infrastructure allowed him to develop an autonomous language. 3. Barragán, a “visual” architect. Barragan defined his work as “autobiographical” and inspired by the colonial villages of his childhood. This is partially true; alongside Mexican architecture, the architect was deeply fond of the timeless aura of vernacular architecture in general. He was thus an enthusiastic reader of Bernard Rudofsky, as well as an omnivorous buyer of books from a wide spectrum of artists like Albres, De Chirico, Matisse, and Delvaux. His own library was a constant source of visual references for the projects. Ultimately, what is today considered the maximum expression of Mexican architecture is in fact the invention of a solitary outsider.